2020
DOI: 10.1002/csr.2024
|View full text |Cite
|
Sign up to set email alerts
|

Code of ethics and workers' communication policies: The role of corporate governance

Abstract: A good monitoring that reduces agency conflicts can help in developing structured policies in code of ethics to help the social information processing for employees. The objective of this research is to investigate whether the corporate governance characteristics, such as duality, board of directors' size and independence as measures of monitor capacity are related to workers' communication policies disclosed in code of ethics. Based on a content analysis of code of ethics to define the latter polices and on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Effective agency theory-based governance can help ensure that tax avoidance strategies do not undermine the company's long-term sustainability or conflict with shareholders' interests (Arifah & Arieftiara, 2021). It reinforces the importance of transparent communication, accountability, and alignment with the company's overall objectives, as guided by agency theory principles, to maintain a healthy and productive relationship between shareholders and management in the context of tax management practices (Furlotti & Mazza, 2020). The fifth hypothesis of this study's moderation test demonstrates that Institutional Ownership does not moderate the link between TCAP on ETR and the decision to avoid taxation.…”
Section: Figure 4 Heteroscedasticity Test Resultsmentioning
confidence: 96%
“…Effective agency theory-based governance can help ensure that tax avoidance strategies do not undermine the company's long-term sustainability or conflict with shareholders' interests (Arifah & Arieftiara, 2021). It reinforces the importance of transparent communication, accountability, and alignment with the company's overall objectives, as guided by agency theory principles, to maintain a healthy and productive relationship between shareholders and management in the context of tax management practices (Furlotti & Mazza, 2020). The fifth hypothesis of this study's moderation test demonstrates that Institutional Ownership does not moderate the link between TCAP on ETR and the decision to avoid taxation.…”
Section: Figure 4 Heteroscedasticity Test Resultsmentioning
confidence: 96%
“…Rodriguez-Dominguez et al (2009) studied the influence of independence and the presence of female members on the board in promoting and hindering the creation of a code of ethics. Furlotti and Mazza (2020) confirmed the close association between board governance and CCE as their study found that the board of directors’ independence is positively related to code of ethics policies related to communication with employees.…”
Section: Literature Surveymentioning
confidence: 85%
“…Table 4 shows the results of the effect of Halal certification on disclosure index. To implement this analysis, we use multivariate regression analysis which allows us to test whether more than one independent variable and more dependent variables are linearly related (Furlotti & Mazza, 2020; Secinaro et al, 2020; Shauki, 2011). Regression investigation suggests a significant and positive relationship between Halal certification and disclosure index.…”
Section: Resultsmentioning
confidence: 99%